MICROWAVE ASSISTED SYNTHESIS OF TETRAHYDROPYRMIDINE AND IN SILICO SCREENING OF ANTIDIABETIC DRUG - S., GEJALAKSHMI; N., HARIKRISHNAN; E., THILLAI GOVINDARAJAN G.; A., DIVYASRI (International Journal of Current Pharmaceutical Research, 2020)
Objective: To detect the microwave-assisted synthesis of Tetrahydropyrimidine derivative and its molecular docking studies for Diabetes. Methods: The Bignelli condensation method was used for Tetrahydropyrimidine derivative synthesis. The docking studies made in Argus Lab software. Results: The Tetrahydropyrimidine is synthesized using the microwave. The Tetrahydropyrimidine derivative is found to be attack the insulin receptor, as it the tendency of binding with insulin receptor showed in Argus lab. Further, the good binding site of Tetrahydropyrimidine derivative with insulin receptor was predicted. Conclusion: From the research work, The Tetrahydropyrimidine derivative shows its affinity to bind with the insulin receptor. The binding value is averagely 7 which indicates it can attraction with the receptor, so it can control Diabetic mellitus by altering insulin secretion in blood plasma.